Utilization of Near Ir Absorbing Gold Nanocolloids by Green Synthesis - Elveren, Beste; Yıldız, Ümit Hakan; Yıldız, Ümit Hakan; Arslan Yıldız, Ahu; Arslan Yıldız, Ahu (Trans Tech Publications, 2018)
The rapid developments in nanoscience, and its applications on biomedical areas have a large impact on drug delivery, tissue engineering, sensing, and diagnosis. Gold is widely investigated nanomaterial for the last couple of decades, since it has unique surface properties and very low toxicity to biological environment. In this work, we present a novel synthesis of gold nanoparticles (GNPs) exhibiting both visible and near-IR absorbance without agglomeration. The surface of GNPs were analyzed by routine methods and the binding kinetics were investigated by Surface Plasmon Resonance (SPR) Spectroscopy. The unique optical properties of near-IR asorbing GNP colloids hold promise for biological applications.
10th Japanese-Mediterranean Workshop on Applied Electromagnetic Engineering for Magnetic, Superconducting, Multifunctional and Nano Materials, JAPMED’10 2017; Izmir; Turkey; 4 July 2017 through 8 July 2017
Keywords: Biofriendly; Flavonoids; Gold nanoparticle; Green synthesis; Plant extract